(untitled) (Bangladesh Journal of Botany, 2008)
A total of 33 hosts from different crop types viz. cereal, pulse, oil, vegetable and fiber plants were tested for pathogenicity in artificially inoculated condition against two isolates (BTB115 and DK64) of Rhizoctonia solani, virulent to potato. In respect of symptoms developed on the stems, the most susceptible hosts against both the isolates were string bean, bottle gourd, groundnut, pea and pumpkin. Soybean stems were highly susceptible to DK64 and less susceptible to BTB115. Disease symptoms did not develop on stems of five crops namely brinjal, proso millet (Panicum miliaceum L.), stem-amaranth, kangkong (Ipomoea reptans L.) and tomato. Symptoms appeared on leaves of all the crops tested. Leaves of groundnut, bush bean, bottle gourd and okra were highly susceptible while those of barley and millet were less susceptible. Â Key words: Rhizoctonia solani, Virulent, Pathogenecity, Crop hosts doi:10.3329/bjb.v37i1.1567 Bangladesh J. Bot. 37(1): 75-80, 2008 (June)